Prevalence of hypodontia in permanent dentition in a sample of Sudanese university students - Amal ABU AFFAN; Abeer SEROUR (International Arab Journal of Dentistry (IAJD), 2014)
The congenital absence of one or more permanent teeth is a common dental anomaly. It can seriously affect a young person, both physically and emotionally, particularly when the missing tooth is located in the anterior region of the maxillary dental arch. The aim of the present descriptive cross-sectional study was to evaluate the prevalence of hypodontia of the permanent dentition and to determine the most common congenitally missing permanent teeth in a sample of 2401 Sudanese university students.A total of 100 congenitally missing teeth were observed in 64 students (7 males and 57 females); the overall prevalence of hypodontia in permanent dentition was 2.66% (2.69% in males, 2.66% in females). Hypodontia was more prevalent in the mandible (61%) than in the maxilla (39%) and in the left side of the jaws (55%) than in the right side (45%). The most common congenitally missing permanent tooth was the mandibular lateral incisor (23%), followed by the maxillary lateral incisor (19%), the mandibular 2nd premolar (18%) and the maxillary 2nd premolar (17%).The present study results give a clue of the magnitude of the problem. However, strong conclusion cannot be drawn since the sample studied is not representative to the whole Sudanese community. Further studies are required with a large sample collected from the different provinces of the Sudan.